Aplikasi Pendataan Jemaat pada GBKP Runggun Diski Berbasis Mobile - Tarigan, Riandi Pratama; Jamaluddin, Jamaluddin; Saragih, Rijois Iboy E. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The Batak Karo Protestant Church (GBKP) Runggun Diski faces challenges in managing congregation data effectively and accurately. Since the data collection process is still done manually, there is a possibility of recording errors, data retrieval issues, and delays in disseminating information to the congregation. To address these problems, this research aims to design and develop a mobile-based congregation data management application. This application will enable church administrators to manage congregation data more efficiently and effectively. During the application development process, the Agile-based software development method allows for continuous iteration and improvement. The application is developed using technologies such as Android-based programming with the Kotlin programming language and Firebase for real-time data storage. The main features of this application include new congregation member registration, worship attendance recording, personal data management of congregation members, and notifications about church activities. The results of this application development indicate that the application runs well on mobile devices and meets the requirements of GBKP Runggun Diski for managing congregation data. It is expected that the use of this application will improve the efficiency of congregation data management, reduce recording errors, and facilitate administrators in delivering information to the congregation. Additionally, the application allows the congregation to access related information more easily than they had previously.